“Die Empörten Weiber”: Gender, Authority and Protestant Modernism in Jeremiah 44 - Sensenig, Melvin L. (Journal for the study of the Old Testament, 2021)
Because of Protestant modernism’s reconstrual of older Protestant views of inspiration around the Romantic notion of the male charismatic prophet, it unintentionally opened doors for the latent gender inequality of its misogynist cultural context when interpreting female religious activity in the prophets. Because of Protestant modernism’s inability to distinguish itself from its 19th-20th century social elite status, it can end up enabling gender stereotypes of its time and thus engage in unexamined gender bias. Vestiges at times remain in literature that assumes the non- or reduced agency of women in Israelite religion. This is a case study in one of the founders of historical-critical Jeremiah study, Sigmund Mowinckel, focusing not on Protestant modernism broadly but rather on Mowinckel’s clear expression of the modernist Protestant notion of the inspiration of sacred speech.